Assessing Galleria mellonella as a preliminary model for systemic Staphylococcus aureus infection: Evaluating the efficacy and impact of vancomycin and Nigella sativa oil on gut microbiota - Faris S. Alnezary; Masaad Saeed Almutairi; Abdullah A. Alhifany; Thamer A. Almangour (Elsevier, 2023)
Background: Staphylococcus aureus is a Gram-positive bacterium that can cause various infections. The Galleria mellonella has been used as a preliminary test for infection model. The study aimed to evaluate the effectiveness of G. mellonella as a microbiome model and compare the efficacy of vancomycin and antimicrobial activity of Nigella sativa (NS) on the gut flora. Methods: G. mellonella larvae were subjected to metagenomic analysis. The larvae's guts were collected, homogenized in phosphate-buffered saline (PBS), and the gut contents isolated for bacterial DNA extraction. Larvae were assigned into the following groups: negative control (PBS only); positive control (MRSA only); vancomycin treated group; NS oil treated group and combination (vancomycin and NS oil) treated group. Larvae were cultured, inoculated with S. aureus, and treated with vancomycin and NS oil. Larval activity, cocoon formation, growth, melanization, and survival were monitored. The toxicity of vancomycin and NS oil was tested, and S. aureus burden and natural microbiota were determined. Hemocyte density was measured. Statistical analysis was conducted using R. Results: Enterococcus related species dominated approximately 90 % of the gastrointestinal tract of the larvae. The survival rate following treatment was 85 % with vancomycin, 64 % with NS oil, and 73 % with a combination of both. The count of Enterococcus Colony Forming Units (CFUs) was significantly lower in the vancomycin treatment group (8.14E+04) compared to those treated with NS oil (1.97E+06) and the combination treatment (8.95E+05). Furthermore, the S. aureus burden was found to be lower in the NS oil (1.04E+06) and combination treatment groups (9.02E+05) compared to the vancomycin treatment group (3.38E+06). Hemocyte densities were significantly higher in the NS oil (8.29E+06) and combination treatment groups (8.18E+06) compared to the vancomycin treatment group (4.89E+06). Conclusions: The study supported the use of G. mellonella model as a preliminary test to assess the effect of different antimicrobials against S. aureus and gut microbiota. NS oil showed more selectivity against S. aureus and protectiveness for the natural Enterococcus gut flora.